2016
DOI: 10.3389/fncir.2016.00001
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Electrophysiological Properties and a Transition from Electrical to Chemical Coupling between Excitatory Layer 4 Neurons in the Rat Barrel Cortex

Abstract: During development, sensory systems switch from an immature to an adult mode of function along with the emergence of the active cortical states. Here, we used patch-clamp recordings from neocortical slices in vitro to characterize the developmental changes in the basic electrophysiological properties of excitatory L4 neurons and their connectivity before and after the developmental switch, which occurs in the rat barrel cortex in vivo at postnatal day P8. Prior to the switch, L4 neurons had higher resting memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 63 publications
(120 reference statements)
3
62
1
Order By: Relevance
“…In vivo recordings that correlate spiking activity of RGC-TC neuron pairs in cats and primates report one or several dominant RGCs that drive TC neuron firing (Cleland and Levick, 1971; Hubel and Wiesel, 1961; Mastronarde, 1992; Sincich et al, 2007; Yeh et al, 2009). However, additional weaker inputs were also found in cat, and notably, most RGCs drive <50% (Range 1–82%) of the postsynaptic spiking of both X and Y neurons (Rathbun et al, 2016; Usrey et al, 1999). These findings are in agreement with the broad distribution of the SF population we show in vitro in mice here and previously (Chen and Regehr, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…In vivo recordings that correlate spiking activity of RGC-TC neuron pairs in cats and primates report one or several dominant RGCs that drive TC neuron firing (Cleland and Levick, 1971; Hubel and Wiesel, 1961; Mastronarde, 1992; Sincich et al, 2007; Yeh et al, 2009). However, additional weaker inputs were also found in cat, and notably, most RGCs drive <50% (Range 1–82%) of the postsynaptic spiking of both X and Y neurons (Rathbun et al, 2016; Usrey et al, 1999). These findings are in agreement with the broad distribution of the SF population we show in vitro in mice here and previously (Chen and Regehr, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…Complex feature selectivity persists in TC neurons after inactivation of the primary visual cortex, suggesting that the dLGN may compute orientation or direction selectivity rather than inherit it from cortical feedback (cat Vidyasagar & Urbas, 1982; mouse Zhao et al, 2013; Scholl et al, 2013). Furthermore, cat TC neurons have a higher stimulus contrast sensitivity than their individual inputs, suggesting TC neurons can functionally integrate information from multiple RGC inputs (Rathbun et al, 2016). The presence of binocularly innervated dLGN neurons in mice, cats, and primates further supports the possibility of convergence of multiple RGCs onto single geniculate neurons in mice, cat, and primate dLGN (Sanderson et al, 1971; Howarth et al, 2014; Zeater et al, 2015; Rompani et al, 2017).…”
Section: More Than a Relaymentioning
confidence: 99%
“…Others, however (especially those focusing on Y cells in cats), show that the contribution from individual RGCs exhibits greater variability, and the activity of a single retinal input rarely accounts for the entirety of the activity of its TC neuron partner (Hubel & Wiesel, 1961; Cleland & Levick, 1971; Cleland et al, 1971; Levick et al, 1972; Mastronarde, 1992). Interestingly, one study using paired recordings across both X- and Y-cells yielded examples of RGCs that drove as few as ~1% to as many as 82% of a TC neuron’s action potentials (Usrey et al, 1999); similar results later emerged in the Y pathway (Yeh et al, 2009; Rathbun et al, 2016; considered in detail in; Weyand, 2016). Furthermore, several studies corroborate anatomical observations of divergence, such that neurons with most closely matching receptive fields exhibit the greatest correlation among their firing patterns (Alonso et al, 1996; Usrey et al, 1998).…”
Section: Retinogeniculate Connectivitymentioning
confidence: 99%
“…The development of quantitative structural imaging techniques to assess the effects of lesion and disease on cognition and behavior (e.g., Bates et al, 2003) has helped to define the limitations and the possibilities for neural plasticity in neurorehabilitation. The ability to evoke long-term changes in cortical excitability (i.e., neural plasticity) using NIBS (Jackson et al, 2016; Lenz & Vlachos, 2016) also has been shows promise of being a game-changing development, and research on the effects of aerobic exercise on cognition in older persons has expanded to become a well-known phenomenon since the meta-analysis of Colcombe and Kramer (2003). Literature in the entire arena of this review is so massive that we cannot fail to disappoint many rehabilitation investigators who read this review because we have not had the space to mention the technique, population, or therapy that is their passion.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there may be critical dose-response effects with cathodal tDCS where a 1 mA current decreases excitability of underlying cortex while a 2 mA current increases excitability (Batsikadze et al, 2013). A final, but important point is that both rTMS (Lenz & Vlachos, 2016) and tDCS (Jackson et al, 2016) have shown lasting changes in cortical excitability indicative of neural plasticity, though much research is needed to characterize these changes.…”
Section: Noninvasive Brain Stimulation and Neural Plasticity: Transcrmentioning
confidence: 99%